PENDIDIKAN SEKSUAL BAGI REMAJA: TANTANGAN DAN HARAPAN DARI PERSPEKTIF ORANG TUA - Munawaroh, Munawaroh (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2023)
This study aims to explore the views of parents in West Java regarding sexual education for adolescents, identify the challenges they face, and understand their expectations for ideal sexual education. Data were collected through semi-structured interviews, participatory observations, and documentation analysis from three purposively selected parents. The results of the study showed that parents face a variety of challenges, including lack of knowledge, awkwardness, and the influence of social and cultural norms that consider sexuality a taboo topic. Nonetheless, they have high expectations for sexual education that can help children understand their bodies, respect personal boundaries, and make wise decisions. This research underscores the importance of external support from schools, governments, and communities to create a comprehensive sexual education curriculum and provide training programs for parents. The limitations of this study include a limited number of samples and a specific geographic focus. Further research is suggested to include a larger and more diverse sample and explore approaches to sexual education that are more inclusive and appropriate to different sociocultural contexts.